Protective effects of hydroalcoholic extract from rhizomes of Cynodon dactylon (L.) Pers. on compensated right heart failure in rats - Kharazmkia Ali; Najafi Moslem; Nazemiyeh Hossein; Afrooziyan Arash; Garjani Alireza; Maleki-Dizaji Nasrin (BMC, 2009)
Abstract Background The rhizomes of Cynodon dactylon are used for the treatment of heart failure in folk medicine. In the present study, we investigated the effects of hydroalcoholic extract of C. dactylon rhizomes on cardiac contractility in normal hearts and on cardiac functions in right-heart failure in rats. Methods Right-heart failure was induced by intraperitoneal injection of monocrotaline (50 mg/kg). Two weeks later, the animals were treated orally with different doses of the extract for fifteen days. At the end of the experiments cardiac functions and markers of myocardial hypertrophy were measured. Results The treated rats showed very less signs of fatigue, peripheral cyanosis and dyspnea. The survival rate was high in the extract treated groups (90%). Administration of C. dactylon in monocrotaline-injected rats led to profound improvement in cardiac functions as demonstrated by decreased right ventricular end diastolic pressure (RVEDP) and elevated mean arterial pressure. RVdP/dtmax, and RVdP/dt/P as indices of myocardial contractility were also markedly (p < 0.001; using one way ANOVA) increased by the extract. The extract reduced heart and lung congestion by decreasing tissue wet/dry and wet/body weight ratios (p < 0.01). In the isolated rat hearts, the extract produced a remarkable (P < 0.001) positive inotropic effect concomitant with a parallel decrease in LVEDP. Conclusion The results of this study indicated that C. dactylon exerted a strong protective effect on right heart failure, in part by positive inotropic action and improving cardiac functions.